Analysis of umbilical cord tissue as an indicator of in utero exposure to toxic adulterating substances - Midthun, Kari M.; Nelson, Brandon N.; Strathmann, Frederick G.; Browne, Thom; Logan, Barry K. (Frontiers in Pediatrics, 2023)
In utero drug exposure is a significant public health threat to the well-being and normal development of the neonate. Recently, testing of umbilical cord tissue (UCT) has been employed to measure illicit drug exposure, as drugs used by the mother during the third trimester may be retained in the UCT. Focus has also been given to potential adverse health effects among drug users, resulting from exposure to pharmacologically active adulterants and cutting agents in the street drug supply. The in utero effects of these substances have not been well studied in humans, nor has their presence been demonstrated as a means for assessing adverse health effects in the neonate. Here, we describe the application of a novel test method to analyze UCT for the presence of more than 20 common adulterating/cutting substances via LC/Q-TOF. In total, 300 de-identified UCT samples were analyzed – all had previously tested positive for cocaine or opiates. Generally, the positivity rates of individual compounds were similar between the Cocaine and Opiates Subgroups, apart from levamisole, xylazine, dipyrone (metabolites), and promethazine. Many of the adulterants used in the street drug supply do have legitimate medicinal/therapeutic uses, including several of the compounds most frequently detected in this study. Caffeine and lidocaine were the most frequently identified compounds both individually (>70% each) and in combination with each other. Alternatively, levamisole, an adulterant with no legitimate therapeutic use, was present in 12% of cases. Importantly, this data demonstrates that the detection of traditional drugs of abuse may serve as indicators of potential in utero exposure to toxic adulterating substances during gestation. While there is cause for concern with respect to any unintentional drug exposure, illicit drug use during pregnancy, including uncontrolled dosing, poly-adulterant consumption, and the interactions of these drug mixtures, produces a significant public health threat to the neonate which warrants further study.